Update on Peripheral Arterial Vasodilation, Ascites and Hepatorenal Syndrome in Cirrhosis - Mladen Knotek; Boris Rogachev; Robert W Schrier (Canadian Journal of Gastroenterology)
In cirrhosis of the liver, according to the peripheral arterial vasodilation hypothesis, relative underfilling of the arterial tree triggers a neurohumoral response (activation of renin-angiotensinaldosterone system, sympathetic nervous system, nonosmotic release of vasopressin) aimed at restoring circulatory integrity by promoting renal sodium and water retention. Evidence has accumulated for a major role of increased vascular production of nitric oxide as the primary cause of arterial vasodilation in cirrhosis. Ascites is a common complication in cirrhosis. Treatment of ascites consists of a low salt diet with diuretics, and paracentesis together with plasma volume expanders in diuretic-resistant patients. Progression of cirrhosis may result in hepatorenal syndrome, a state of functional renal failure that carries an ominous prognosis. Orthotopic liver transplantation has remained the only curative treatment for patients with advanced liver disease; other modalities such as transjugular intrahepatic portosystemic shunt or vasopressin analogues may serve as a bridge to transplantation. Another complication of decompensated cirrhosis is spontaneous bacterial peritonitis, the incidence of which can be reduced by primary or secondary antibiotic prophylaxis by using orally active antibiotics.